Parental Behaviors and Social Skills in Secondary Education Students of Callao - Madueño Ramos, Percy (2020)
The purpose of the study is to establish the relationship between the perception of parental behaviors and social skills in a sample of 280 students, between 11 and 14 years, of a State Educational Institution of the Constitutional Province of Callao. There is a direct relationship between the adolescents' perception of the positive parenting practices of the father and the mother with the presence of social skills. The result of the study is due to social desirability, where adolescents seek to transmit a culturally acceptable image and avoid criticism. The implications of the results are discussed in terms of the objectives set, the social reality and the cultural reality of our country.